Future development trends in CAM/CAPP–NC systems. (4th August 2014) - Fuh, J.Y.H.; Ji, P.; Zhang, Y.F.
CAD/CAM integration is regarded as a solution for bridging the gap between design and manufacturing, one of the ultimate goals for concurrent engineering. Computer–aided process planning (CAPP) and automated NC part programming are the two key elements in the modern CAM systems. Reviewing the current status of CAM development, this paper highlights some of the key issues along with its evolving trends. It is observed that Integration and Intelligence are driving the present research and development for CAM systems. With the increasing use of more advanced AI techniques, feature technology and user–friendly interfaces, the next generation CAM (NEG–CAM) systems will have a complete new look. We give a perspective on the NEG–CAM systems focused on process planning and NC tool path generation. The method of task planning is introduced for the integration of CAPP and NC functions.